DEGRADASI KOLESTEROL DAN KOPROSTANOL DALAM SEDIMEN SUNGAI - Iryanti Eka Suprihatin (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2010)
Cholesterol and other steroid compounds like coprostanol, epicoprostanol, have been used as sourceindicator for fecal pollution in aquatic environments. This is because of the unique steroid composition of animalfeces. To determine the source of fecal pollution, the ratios of steroid compounds in the sample are used. Thus anyreaction or changes to any steroid compound in the environment will affect the determination. In this paper a studyon the interconversion of cholesterol and coprostanol in river sediments is reported. The study suggests that there isno such changes that any steroid compounds detected in a sediment sample will show their primary sources. Thisimplies that the composition or ratio of the compounds can be used as source indicator for fecal pollution. The studyalso found that both cholesterol and coprostanol degradation are first order with rate constants of0,063[kolesterol]mgL-1day-1 and 0.045[kop]t mgL-1day-1 respectively.